Methods, implementation, and application of cyber security intelligence and analytics - Jena, Om Prakash; Gururaj, H. L., 1988-; Pooja, M. R., 1982-; Kumar, S. P. Pavan, 1989- (Advances in information security, privacy, and ethics (AISPE) book series., 2022)
"This book looks at the intersection of Artificial Intelligence and Cyber security which has emerged as one of the most promising use cases for the advancement of Cyber security in the technological age"--